2017
DOI: 10.3892/etm.2017.5248
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA HOTAIR promotes the proliferation and metastasis of osteosarcoma cells through the AKT/mTOR signaling pathway

Abstract: It has been proven that long non-coding (lnc)RNAs serve an important role in the tumorigenesis and development of several types of human malignancy. Previous studies have demonstrated that the lncRNA Hox transcript antisense intergenic RNA (HOTAIR) is involved in the development various types of cancer, including osteosarcoma (OS). However, the underlying mechanisms by which it has an affect are still largely unknown. In the present study, it was observed that the expression of HOTAIR was significantly upregul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 30 publications
3
26
0
Order By: Relevance
“…Consistent to this hypothesis, findings revealed that down-regulation of HOTAIR could promote G1 cell cycle arrest [49]. So that, loss of this lin-cRNA promote expression of p27 leading to binding and prohibiting Cyclin D-CDK4 and Cyclin E-CDK2 activities [49] (Fig. 3).…”
Section: Function Of Hotair In Normal Developmentsupporting
confidence: 67%
See 2 more Smart Citations
“…Consistent to this hypothesis, findings revealed that down-regulation of HOTAIR could promote G1 cell cycle arrest [49]. So that, loss of this lin-cRNA promote expression of p27 leading to binding and prohibiting Cyclin D-CDK4 and Cyclin E-CDK2 activities [49] (Fig. 3).…”
Section: Function Of Hotair In Normal Developmentsupporting
confidence: 67%
“…Collaboration of Cyclin D1 with CDK4 and CDK6 contributes to posttranslational phosphorylation of some proteins and activity of some necessary transcription factors for transition of G1 to S cell cycle [48]. Consistent to this hypothesis, findings revealed that down-regulation of HOTAIR could promote G1 cell cycle arrest [49]. So that, loss of this lin-cRNA promote expression of p27 leading to binding and prohibiting Cyclin D-CDK4 and Cyclin E-CDK2 activities [49] (Fig.…”
Section: Function Of Hotair In Normal Developmentsupporting
confidence: 59%
See 1 more Smart Citation
“…It has been reported that lncRNAs can affect cell activities in human cancers by regulating the signal of some signaling pathway. For instance, lncRNA HOTAIR could activate the AKT/ mTOR signaling pathway, thereby enhancing the proliferative or migratory ability of osteosarcoma cells; 33 LncRNA MRCCAT1 improves cell metastasis in clear cell renal cell carcinoma by activating p38-MAPK signaling; 34 LncRNA HNF1A-AS1 has also been proved to be able to interact with Wnt/beta-catenin signaling pathway in both colorectal cancer 35 and osteosarcoma. 36 Notch signaling pathway is widely considered as a highly conserved cell signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…18 Previous studies have revealed that the PI3K/Akt/mTOR pathway is particapted in the development of OS. For example, Li X et al 29 have reported that LncRNA HOTAIR could promote cell progression through Akt/mTOR pathway in OS. Furthermore, according to reports demonstrated, MDA19 could suppress the downstream protein of PI3K/Akt/mTOR pathway in OS, such as Cyclin D1, P70S6K and p-P70S6K.…”
Section: Discussionmentioning
confidence: 99%